Lithofacies interpretation and depositional model of Talangakar Lacustrine Deposits: A Study in the Ardjuna Field, Eastern Sunda Basin - Ismanto, Aviandy Widya; Feraldo, Ridho; Akbar, Afriyan; Suhartomo, Herry; Hasani, Nurul; Musakti, Oki Trinanda; Wasonoaji, Andi; Saputra, Lulus Ilmiawan (Berita Sedimentologi, 2024)
The Ardjuna Field in the Northwest Corner (NWC) block is located on the eastern side of Sunda Basin and is adjacent to the Seribu Fault. Producing reservoirs in the Ardjuna Field are mainly of the Talangakar (TAF) fluvio-deltaic sandstones, however all wells within the four production platforms of the field had been shut in November 2006. Hence it is necessary to re-evaluate remaining potential and to seek new reservoirs within the field in order to reactivate oil and gas production from the structure.The main focus of our study is to evaluate the remaining potential of TAF fluvio-deltaic producing zones and identify new potential in the TAF lacustrine deposits. We used a total of 8 exploration wells, 17 development wells, and a 3D seismic dataset during our evaluation. Out of the 25 wells, only two wells have penetrated the lacustrine deposits interval, i.e. W-1 and S-5 wells. The S-5 well proved flowing HC of up to 1,043 MMCFGPD and 332 BOPD from DST.The lower TAF lacustrine deposit is characterized by the occurrence of typical freshwater pollens, displaying a serrated and coarsening upward log pattern, thin succession, and absence of sediment structures. Seismic interpretation and Acoustic Impedance (AI) analysis indicate that low AI value ( 7200 gr/cc*ft/s) correlate with high porosity, interpreted as sandstone. The AI-guided seismic attribute reveals a relatively regular lobate shape resembling a fan measuring 1.7 km by 2.5 km. Furthermore, low AI values are more prevalent and widely distributed, particularly on top of the closure.